Earnings Manipulation Analysis Using Beneish M-Score in Textile and Garment Companies on IDX 2020-2024 - Novi Purwaningsih; Nur Anisah (Asosiasi Pengelola Publikasi Ilmiah (APPI) PT PGRI, 2025)
This study aims to analyze the application of the Beneish M-Score Model in detecting indications of earnings manipulation in textile and garment companies listed on the Indonesia Stock Exchange for the 2020-2024 period. The Indonesian textile industry is facing a structural crisis with 60 companies closing since 2022, mass layoffs reaching 80,000 workers, and factory utilization dropping to 45-50%. The results show that of the 15 sample companies, 7 companies (46.67%) are indicated to have engaged in earnings manipulation based on the M-Score threshold > -2.22, namely Inocycle Technology Group, Asia Pacific Investama, Pan Brothers, Century Textile, Eratex Djaja, Asia Pacific Fibers, and Sunson Textile. The companies with the highest risk are Inocycle Technology Group (maximum M-Score 39.07), Asia Pacific Investama (maximum M-Score 54.78), and Pan Brothers (maximum M-Score 26.60). Trend analysis shows a pattern of progressive deterioration in several companies in line with worsening industry conditions. The TATA (Total Accruals to Total Assets) and DSRI (Days Sales in Receivables Index) components are the dominant indicators of manipulation. This research provides practical contributions for investors, creditors, and regulators in identifying early warning signals related to the quality of financial reporting.